ANALYSING THE SIDE EFFECT OF AMIODARONE N CONSUMPTION ON OPTIC NERVE HEAD, CONTRAST SENSITIVITY AND COLOR VISION IN ARRYTHMIA PATIENT: Oral Presentation - Observational Study - Resident - Callina Floriana Y. Br. Bangun; Bobby Ramses Erguna Sitepu; Delfi (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To analyze the side effect of duration consumption of amiodarone on ONH, contrast sensitivity and color vision in arrythmia patient Methods : This study was an analytical observational study with cross sectional design. A total of 23 subjects with arrhythmias taking amiodarone were included in the study. Sampling was carried out from April 2022-August 2022 at the Eye Polyclinic and Cardiology Polyclinic. Results : Most of the subjects were female, 12 people (52.2%) with a mean age of 59 years. The results of the examination showed that two subjects had decreased vision, ONH edema and decreased contrast sensitivity in the right eye where the mean duration of amiodarone consumption was 4.5 months. The results of binocular color vision examination were normal in all study subjects. There was a significant effect of the consumption duration of amiodarone on ONH (p=0.024) and on contrast sensitivity (p=0.022) Conclusion : There was a significant effect of the duration consumption of amiodarone on ONH and contrast sensitivity in arrythmia patient